DISTRIBUSI ZAKAT DALAM BENTUK PENYERTAAN MODAL BERGULIR SEBAGAI ACCELERATOR KESETARAAN KESEJAHTERAAN - Wibowo, Arif (JURNAL ILMU MANAJEMEN, 2015)
The study discusses the zakat distribution on the effect of wellbeing equality by using the rolling capital investments. It is believed that zakat have a role to increase well being of citizen. However it have been yet managed well professionally. Hence, it is proposed that zakat distrubution able to improve wellbeing equality if it is managed as capital investment which applied in a proper way.